Corporate expenditures on R&D - Żukowski, Marek; Białek-Jaworska, Anna (Research Papers of Wrocław University of Economics, 2018)
The study identifies factors determining accounting policy in respect to signaling results of undertaken R&D activity. Under International Financial Reporting Standards there is a choice between the capitalization of R&D expenses in the form of intangible assets or treating them as reporting period costs thus decreasing financial result. In order to test if the decision to capitalize development expenditures is a way of signaling the success of undertaken research and development (R&D) activity to the stakeholders, a logistic regression analysis was performed on a sample of 112 non-financial firms listed on the WSE in 2010–2013. Development of enterprises in the global market depends on the implementation of innovative products and services. This can be achieved through the use of available intellectual resources and by investing in the R&D activity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 65-75
Keywords: R&D; B+R; capitalization; innovations; disclosure; kapitalizacja; innowacje; ujawnienia informacji